Systemic sclerosis: A world wide global analysis (2009)
The objective of this study was to analyze epidemiological tendencies of systemic sclerosis (SSc) around the world in order to identify possible local variations in the presentation and occurrence of the disease. A systematic review of the literature was performed through electronic databases using the keywords 'Systemic Sclerosis' and 'Clinical Characteristics.' Out of a total of 167 articles, 41 were included in the analysis. Significant differences in the mean age at the time of diagnosis, subsets of SSc, clinical characteristics, and presence of antibodies were found between different regions of the word. Because variations in both additive and nonadditive genetic factors and the environmental variance are specific to the investigated population, ethnicity and geography are important characteristics to be considered in the study of SSc and other autoimmune diseases. © Clinical Rheumatology 2009.